CTNI-25. PHASE IB CLINICAL TRIAL OF CHRONIC CONVECTION-ENHANCED DELIVERY OF TOPOTECAN FOR RECURRENT GLIOBLASTOMA. (9th November 2020) - Bruce, Jeffrey; Spinazzi, Eleonora; Lassman, Andrew; Iwamoto, Fabio; Welch, Mary; Banu, Matei; Argenziano, Michael; Upadhyayula, Pavan; Agar, Nathalie Y R; Humala, Nelson; Marie, Tamara; Pereira, Brianna; et al.
Abstract: OBJECTIVES: Convection-enhanced delivery (CED) provides pharmacokinetic advantages over systemic delivery for achieving cytotoxic drug levels into targeted regions of the brain. A major shortcoming of CED has been the need to limit treatment duration because of infection risks associated with external pumps. We engineered a subcutaneously implanted catheter-pump construct for prolonged CED which was successfully tested in a large animal model and then approved by the FDA for a Phase Ib clinical trial with topotecan in patients with refractory glioblastoma (IND 131889). METHODS: Five patients with recurrent glioblastoma underwent surgical implantation of a subcutaneous pump and catheter that infused intracerebral topotecan over 30 days. Gadolinium was co-infused as a surrogate tracer and advanced non-invasive radiographic imaging was used to monitor drug distribution and pharmacological effects. Tissue from multiple radiographically-localized regions of each tumor and surrounding brain was procured pre-treatment at the time of catheter implantation and then post-treatment when tumors were surgically resected. Tissue was used for drug level measurements and advanced molecular, genomic and cellular analysis of treatment effects. RESULTS: Treatments were successfully completed in all five patients without significant complications. The safety and tolerability of treatment was validated by quality-of-life measures and neurological assessments. Noninvasive imaging demonstrated large and stable drug distribution volumes. Comprehensive tissue analysis demonstrated effective targeting of mitotically active tumor cells while sparing neurons. CONCLUSIONS: We engineered a subcutaneously implanted catheter-pump construct for chronic CED that was successfully tested in a Phase Ib clinical trial with topotecan in recurrent glioblastoma patients. Analysis of pre- and post-treatment tissue showed significant anti-tumor activity from topotecan that was not harmful to normal brain. Chronic CED combined with non-invasive real time drug distribution monitoring provides a safe and effective glioma strategy suitable for clinical use.